Longitudinal survey of Clostridium difficile presence and gut microbiota composition in a Belgian nursing home. Issue 1 (December 2016) - Rodriguez, Cristina; Taminiau, Bernard; Korsak, Nicolas; Avesani, Véronique; Van Broeck, Johan; Brach, Philippe; Delmée, Michel; Daube, Georges
Abstract Background Increasing age, several co-morbidities, environmental contamination, antibiotic exposure and other intestinal perturbations appear to be the greatest risk factors forC. difficile infection (CDI). Therefore, elderly care home residents are considered particularly vulnerable to the infection. The main objective of this study was to evaluate and follow the prevalence ofC. difficile in 23 elderly care home residents weekly during a 4-month period. AC. difficile microbiological detection scheme was performed along with an overall microbial biodiversity study of the faeces content by 16S rRNA gene analysis. Results Seven out of 23 (30.4 %) residents were (at least one week) positive forC. difficile. C. difficile was detected in 14 out of 30 diarrhoeal samples (43.7 %). The most common PCR-ribotype identified was 027. MLVA showed that there was a clonal dissemination ofC. difficile strains within the nursing home residents. 16S-profiling analyses revealed that each resident has his own bacterial imprint, which was stable during the entire study. Significant changes were observed inC. difficile positive individuals in the relative abundance of a few bacterial populations, includingLachnospiraceae andVerrucomicrobiaceae. A decrease ofAkkermansia in positive subjects to the bacterium was repeatedly found. Conclusions A highC. difficile colonisation in nursing home residents was found, with a predominance of the hypervirulent PCR-ribotype 027. PositiveC. difficile status is not associated with microbiota richness or biodiversity reduction in this study. The link betweenAkkermansia, gut inflammation andC. difficile colonisation merits further investigations.